Gender and Sexual Diversity Observatory. Incorporating a gender perspective at the Universidad Nacional del Sur (Bahía Blanca, Argentina) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
The Gender and Sexual Diversity Observatory (OGDS) is an Outreach Project that began in 2017 in the Department of Health Sciences of the Universidad Nacional del Sur, Bahía Blanca, Argentina. It is comprised of an interdisciplinary team from different departments at the university. The aim of this article is to systematize the experience of the OGDS as an outreach project and reflect on the role of the gender perspective in university education and practices, as well as to present research with a gender perspective conducted by the OGDS. To this end, it is necessary to consider the fluctuations in the political context and their impact on the incorporation of the gender perspective at the UNS. A pending challenge is to achieve greater institutionalization of the OGDS to consolidate it as a formal space within the University. It is urgent to strengthen these spaces for struggle to counter the hate speech that deeply shapes the subjectivities of children, adolescents and young people.
Keywords: university outreach; gender perspective; gender mainstreaming; inclusive gender policies